Fluctuating neurological symptoms: should I call the neurologist or the hematologist? - Losa-Rodríguez Rita (De Gruyter, 2020)
The objective of this study was to highlight the role of the clinical laboratory and the relevance of reporting the case immediately to the unit of hematology for the diagnosis and early administration of treatment in the presence of such an urgent hematologic disease as thrombotic thrombocytopenic purpura (TTP).